A method to purify recombinant nucleocapsid protein of Nipah virus using hydrophobic interaction chromatography. - Tey, Beng Ti; Chong, Fui Chin; Tan, Wen Siang (2012)

(untitled)
The invention provides a method to purify a recombinant virus protein from microbial cells. Hydrophobic interaction Chromatography (HIC) is used to capture recombinant virus protein from both clarified and unclarified microbial cell lysate.